The potential impact of the proposed regulations on the alcohol market in South Africa. - Maharaj, Shivani (My University, 2014)
ABSTRACT Alcohol abuse is a major problem in South Africa and across the world. It diminishes mental capital, as well as places heavy financial and social burdens on the state and the affected communities. It is, therefore, vitally important that irresponsible alcohol consumption be curbed. Critics of alcohol advertising argue that advertising and marketing of alcoholic beverages increases alcohol consumption, which, in turn, increases alcohol abuse and the fatalities associated with it. A number of researchers have confirmed that advertising is a factor that may influence alcohol consumption, but the same number of researchers has proven otherwise. This study assessed the effectiveness of the proposed regulations on reducing alcohol consumption in the country and it found that the alcohol market size would not diminish if mainstream advertising were banned. The study was exploratory in nature. The data was collected through in-depth interviews with a convenience sample of experts and was analysed using direct content analysis. The research did find that a ban on above-the-line advertising would affect the alcohol market size and structure. The research was inconclusive with regard to the effect of the ban on competition within the industry. However, it found that the market size and total alcohol consumption are unlikely to be impacted.
MBA 2012
Keywords: Alcoholic beverage industry, Alcohol -- Law and legislation, Advertising -- Alcoholic beverages, Liquor laws .